2017
DOI: 10.14429/dlsj.2.10370
|View full text |Cite
|
Sign up to set email alerts
|

ANN based Joint Time and frequency analysis of EEG for detection of driver drowsiness

Abstract: Drowsiness detection plays a vital role in accidents avoidance systems, thereby saving many precious lives. Many attempts were made to detect the drowsiness by the physiological features such as Electroencephalogram (EEG), Electrooculogram (EOG), and Heart Rate Variability, etc., but a reliable index to determine the drowsiness is not yet a reality. This study contributes in identifying the drowsiness levels by an index called Drowsiness Index (DI) from the EEG signal analysis of the drivers. In this report, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The β activity corresponds to the frequency band [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz. It is present on both sides of the brain symmetrically.…”
Section: Betamentioning
confidence: 99%
See 1 more Smart Citation
“…The β activity corresponds to the frequency band [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Hz. It is present on both sides of the brain symmetrically.…”
Section: Betamentioning
confidence: 99%
“…The main difference between all approaches using neural networks lies in the nature of the inputs used as well as the type of network used. Authors of [25]suggested applying a PCA to a three-channel EEG spectrum to drive a multilayer neural network on the main component spectrum.Authors of [26]estimated the EEG spectrum by both STFT and WT to drive their network. Their technique has not been tested on real signals.Authors of [27] used a single parieto-occipital EEG channel (P4-O2) to educate two different networks.…”
Section: Detection Systemsmentioning
confidence: 99%